The school evaluation and improvement plans in Extremadura: the role of the Educational Inspectorate - García Zapata, José Félix (Avances en Supervisión Educativa, 2023)
The aim of this paper is to list the different actions contained in the action plans of the Education Inspectorate in Extremadura related to the evaluation of schools. For this purpose, this paper reviews the activities of different administrative units related to school evaluation, in accordance with the functions attributed by the autonomous educational regulations of Extremadura. It also refers to the so-called "Plan for the improvement of educational success" established in 2011 by the Education Act of Extremadura, assessing its limited practical development. Finally, and in the absence of being able to present a plan for the evaluation of schools established by the educational administration in Extremadura, a review is made of the different common and priority actions with a more or less direct relationship with the evaluation of schools contained in the current institutional plans of the education inspectorate in Extremadura: The Master Plan 2023-2026 and the Annual General Plan 2023/24. An unavoidable mention is included of an Erasmus+ project, directly related to school evaluation and improvement plans, in which the education inspectorate of Extremadura has participated. The work ends with the contributions of the education inspectorate to the internal evaluation of schools in Extremadura.